Alveolar and gingival necrosis resulting from chloroform overextrusion beyond the root canal: A case report - Zahra Sadat Modarresi; Sahar Shafagh; Mehrzad Kaviani; Mojtaba Salehi Karizmeh (Clinical Case Reports)
Key Clinical Message Chloroform is among the most common solvents for root canal treatment. Despite its classification as a potential carcinogen, it is effective if used correctly. Inappropriate use can lead to severe complications, including persistent pain, gingival recession, and necessitating surgical intervention to resect necrotizing bone.